LIPOSOMES IN COSMETIC SCIENCE: A COMPREHENSIVE REVIEW OF APPLICATIONS AND BENEFITS (The Research of Medical Science Review, 2025)
Targeted drug delivery in cosmetics and dermatology aims to maximize the efficacy and localization of active ingredients while overcoming the skin's natural barrier, particularly the stratum corneum. Lipid-based carriers such as liposomes offer a biocompatible, non-toxic, and effective strategy for enhancing dermal and transdermal delivery. Liposomes encapsulate both hydrophilic and lipophilic substances, facilitating controlled release, reduced systemic absorption, and improved skin hydration, protection, and repair. Various specialized liposomal systems—including transferosomes, niosomes, novasomes, marinosomes, ultrasomes, photosomes, ethosomes, phytosomes, yeast-based liposomes, sphingosomes, glycerosomes, oleosomes, catezomes, and invasomes—have been developed to address specific delivery challenges and skin concerns such as acne, dryness, UV damage, inflammation, and aging. These systems leverage diverse compositions and mechanisms to improve skin penetration, stability, bioavailability, and therapeutic outcomes. The continued evolution of liposomal technologies supports the development of advanced cosmeceuticals with enhanced performance, safety, and consumer acceptance.